C-101 Production and properties of SOSIP trimers. (April 2018) - Moore, John
Abstract : I will review the progress of our team's projects to produce GMP-quality SOSIP trimers in amounts and quantities appropriate for human clinical trials. The BG505 SOSIP.664 GMP-project has now been completed successfully, yielding 5 g of trimers. A follow-up on effort to make the germline–bNAb targeting BG505 SOSIP. v4.1-GT1.1 trimer is well underway, using the same core methodologies. The latter trimer was designed at the Amsterdam Medical Center and is very similar to one recently described by Medina-Ramirez et al in J Exp Med. This project stems from our NIH-funded HIVRAD grant program and the translation phase has been supported and managed by the BMGF and IAVI, reflecting the three funding agencies working together towards a common goal.